Exploring factors for melodic diversification of folk songs in the Ryukyu Archipelago - Nishikawa, Yuri; Ihara, Yasuo (Evolutionary human sciences, 2025)
Cultural evolution of traditional music around the world has been the subject of recent quantitative investigations. Researchers have explored cultural diffusion of music as well as patterns of geographic variation that may result. By comparison, less has been studied about the process of music diversification; in particular, under what circumstances music diversifies is yet to be understood. In this study, we examine possible factors that may facilitate music diversification, using data from folk songs in the Ryukyu Archipelago, south-western islands of Japan. For a quantitative analysis, we first transform the melody of each folk song, following an automated scheme, into a sequence of alphabets, which is then used to quantify the melodic dissimilarity between each pair of songs. Our particular interest is in the dissimilarity between putative sister songs, or songs that are inferred to have derived from a common origin, and factors that have positive or negative effects on it. Our results suggest that sister songs tend to diversify more when they are sung in different islands, probably as a result of one being transmitted from one island to another, and when they have come to be sung in different social contexts.